2018
DOI: 10.1007/s40273-018-0662-1
|View full text |Cite|
|
Sign up to set email alerts
|

Novel Risk Engine for Diabetes Progression and Mortality in USA: Building, Relating, Assessing, and Validating Outcomes (BRAVO)

Abstract: The BRAVO risk engine for the US diabetes cohort provides an alternative to the UKPDS risk engine. It can be applied to assist clinical and policy decision making such as cost-effective resource allocation in USA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
90
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(92 citation statements)
references
References 39 publications
2
90
0
Order By: Relevance
“…Along with early diagnosis, people with T2D now have a longer life expectancy compared with just a few decades ago, which emphasizes the need for a continued effort to ensure optimal glycaemic control to prevent diabetes‐related complications. By applying simulations and machine learning methods, trajectories of HbA1c have been predicted, but these models have been developed and validated using RCT data or country‐specific cohorts, thereby limiting their generalizability and application in a real‐world setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Along with early diagnosis, people with T2D now have a longer life expectancy compared with just a few decades ago, which emphasizes the need for a continued effort to ensure optimal glycaemic control to prevent diabetes‐related complications. By applying simulations and machine learning methods, trajectories of HbA1c have been predicted, but these models have been developed and validated using RCT data or country‐specific cohorts, thereby limiting their generalizability and application in a real‐world setting.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of diagnostic and prognostic prediction models have been proposed in the area of diabetes medicine; most of them have focused on diabetes prevention and diagnosis or prediction of diabetes‐related complications . Few models have been developed for the prediction of glycaemic control in subjects with diabetes, and while some apply to people with type 1 diabetes (T1D), those for people with T2D focused on the trajectory of HbA1c predicted through simulation, or by using machine learning methods; these studies, however, used data from RCTs or a single‐country cohort, thus limiting the generalizability of the findings. Moreover, to our knowledge, no models have been developed to predict the durability of glycaemic control in people with T2D after metformin failure, thereby leaving the individual decision to the single healthcare professional.…”
Section: Introductionmentioning
confidence: 99%
“…Several other models have been so far described to predict all-cause mortality in patients with type 2 diabetes (5,6,(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). Some of them lack formal, independent and external validation (20-24).…”
Section: Discussionmentioning
confidence: 99%
“…Some other models were based on simulation studies, with the model's prognostic accuracy being, unfortunately, not reported (25)(26)(27)(28). In addition, many models have been built based on clinical trial data (25,28,30), which leaves the question open as to their transportability to real-life settings. Finally, several studies (5, 6, 21-23, 25, 28-30) included patients of different ethnicity, which makes it impossible to obtain population specific models.…”
Section: Discussionmentioning
confidence: 99%
“…In 2018, Shao et al participated the 9th Mt. Hood Challenge to demonstrate that their BRAVO microsimulation model of diabetes costs and outcomes, 29 based on the publicly available ACCORD patient-level clinical trial data, performs much better on many, if not all, dimensions than other advanced diabetes models, all of which are based on the much older UKPDS data. 30 In development of BRAVO, Shao et al devised a novel approach to estimate regional multipliers for diabetes models that are constructed using data from a single region, thereby improving prediction accuracy by reducing systematic bias and increasing explanation power.…”
mentioning
confidence: 99%